Meneropong Upaya Qur’anisasi Masyarakat Kampung di Ujung Timur Pulau Jawa (Studi Living Qur’an) - Puput Lestari (AQWAL Journal of Qur'an and Hadis Studies, 2021)
This article is an observation that the author made while in Banyuwangi.Banyuwangi, which historically was a city that used to be predominantly Hindu, hasnow turned into a predominantly Muslim and religious city. This study focuses onobserving the habit of reading the Koran in the community of one of the villages inBanyuwangi. Some observations were made in the month of Ramadan, and somewere carried out outside the month of Ramadan. Then in collecting data, the authorconducted interviews with one of the local Koran teachers and some of theobservations made by the authors when participating in some of these activities.From the results of research and observations made by the author, it turns out thatthere is an interesting side that displays the piety of the villagers. Among them, theapplication of the practice of the values of the Koran through the reading of theKoran in various forms and is considered the heart of worship. The various forms ofreading the Koran start from reading the Koran in the month of Ramadan combinedwith local cultural traditions, and several sima'an Koran assemblies that wereestablished collectively that have a unique and distinctive feel.